Zulfi Bhutto of Pakistan : His Life and Times - Wolpert, Stanley (Karachi Oxford University Press, 2007)
No individual in the history of Pakistan - indeed, few people in modern history - have achieved greater popular power or suffered so ignominious a death as Zulfikar Ali Bhutto. Bhutto's political rise and fall were so meteoric that his name became a legend in the land he once ruled. Indeed, a full decade after his execution his continuing popularity ensured the election of his daughter, Benazir, to the premier position he once held. As she campaigned in Sind and Punjab, the crowds cried "Jiye Bhutto!"--"Bhutto Lives!"--and the Bhutto they meant was Zulfi. Zulfi Bhutto of Pakistani tells the story of this remarkable life in a vivid, insightful narrative. Written by Stanley Wolpert, a leading authority on South Asia and the author of the acclaimed biography Jinnah of Pakistani, the volume traces the life of this remarkable figure front the colorful days of his feudal ancestors to his imprisonment and hanging at the hands of a military dictatorship. Bhutto, Wolpert writes, was a charismatic and contradictory man, a microcosmic reflection of Pakistan itself - a nation bond out of division with India which later fell victim to its own internal split with the creation of Bangladesh. Wolpert follows him from his privileged youth in British-ruled India, to his years as a student at the University of Southern California and University of California, Berkeley (where he sported a thin moustache, shiny two-tone shoes, and proved a keen, if rakish, fraternity brother), to Oxford and back to Pakistan. Bhutto climbed to the heights of power with amazing swiftness, winning a seat in the central Cabinet of Pakistan at the unprecedented age of thirty. Wolpert weaves Pakistan's turbulent politics and repeated wars with India together with Bhutto's ambitious maneuvering, tracing his rise to Foreign Minister, the founding of his own political movement, and finally leadership of the nation. The story of Bhutto's sometimes inspiring, sometimes quixotic career is a fascinating one, and Wolpert tells it brilliantly, through Bhutto's triumphant years in the mid-1970s, the military coup in 1977, and his treacherous imprisonment and execution in 1979. Like the nation he embodied, Bhutto led a sprawling, ambitious, and tragic existence. Wolpert's intensively researched, engagingly written account captures the scheming, the grandeur, and the contradictions of one of modern history's most fascinating figures.
Include Color Illustrations, Notes, Bibliography and Index
Keywords: Bhutto, Zulfikar Ali, 1928-1979 -- Prime ministers